Effectiveness of raw robusta coffee bean solution and coffee instant robusta to plaque - Muchlisha, Adila; Rusminah, Nunung; Rachmawati, Emma (Padjadjaran Journal of Dentistry, 2014)
Introduction: It is known that coffee bean consists of higher tannin and trigonelin than instant. Those substances have a role to hamper plaque formation by preventing bacteria sticking on peliccle. The study was conducted to find out the efectiveness of raw robusta coffee bean solution and instant robusta coffee powder toward plaque. Methods: This study was a quasi experimental study with purposive sampling method. The total sample was 20 women who were between 20-30 years old. The plaque was assessed by Personal Hygiene Performance (PHP) plaque index from Podshadley and Haley. Results: There is a different plaque index after gargling with raw robusta coffee bean solution and instant robusta coffee powder solution with plaque index rate differences are 0.6990 and 1.1828, p=0,000.Conclusion: The solution of raw robusta coffee beans is more effective in preventing the formation of plaque than instant robusta coffee powder solution.